Relevance of liver surface nodularity for preoperative risk assessment in patients with resectable hepatocellular carcinoma. Issue 7 (2nd March 2020) - Hobeika, C; Cauchy, F; Sartoris, R; Beaufrère, A; Yoh, T; Vilgrain, V; Rautou, P E; Paradis, V; Bouattour, M; Ronot, M; Soubrane, O
Abstract: Background: Quantification of liver surface nodularity (LSN) on routine preoperative CT images allows detection of cirrhosis and clinically significant portal hypertension. This study aimed to assess the relevance of LSN in preoperative assessment of operative risks for patients with resectable hepatocellular carcinoma (HCC). Methods: All patients undergoing hepatectomy for HCC between 2012 and 2017 were analysed retrospectively. LSN was assessed at the liver–fat interface on the left liver lobe on preoperative CT images. The feasibility of LSN quantification was assessed. The association between LSN and outcomes (severe complications and posthepatectomy liver failure (PHLF)) was evaluated by multivariable analysis and after propensity score matching. Results: Among 210 patients, LSN measurement was successful in 187 (89·0 per cent). Among these, the median LSN score was 2·42 (i.q.r. 2·21–2·66) and 52·9 per cent had severe fibrosis, including 33·7 per cent with cirrhosis. LSN score increased with hepatic venous pressure gradient ( P = 0·048), severity of steatosis ( P = 0·011) and fibrosis grade ( P = 0·001). LSN score was independently associated with severe complications (odds ratio (OR) 5·25; P = 0·006) and PHLF (OR 6·78; P = 0·003). After matching with respect to model for end-stage liver disease, aspartate aminotransferase-to-platelet ratio index and fibrosis-4 score, patients with a LSN score of 2·63 or higher retained an increased risk of PHLF (OR 5·81; P = 0·018). In the subgroup of patients without severe fibrosis, LSN was accurate in predicting severe complications ( P = 0·005). Patients with ( P = 0·039) or without ( P = 0·018) severe fibrosis with increased LSN score had a higher comprehensive complication index score. Among patients with cirrhosis who had clinically significant portal hypertension, a LSN value below 2·63 ruled out the risk of PHLF. Conclusion: LSN measurement represents a practical tool that may allow improvement in the preoperative evaluation and management of patients with HCC. Graphical Abstract: Liver surface nodularity (LSN) quantification on routine preoperative CT images allows detection of cirrhosis and clinically significant portal hypertension. In 187 patients with resectable hepatocellular carcinoma (HCC), LSN was associated with severe postoperative complications and predicted liver failure independently of preoperative liver biology. This study showed that LSN is a practical tool, which may allow improved preoperative evaluation and management of patients with HCC. Suitable for risk assessment